Effects of Mercury(II) Chloride and Osil® (OsilR) on Node Surface Sterilization of Hom (𝙎𝙩𝙧𝙤𝙗𝙞𝙡𝙖𝙣𝙩𝙝𝙚𝙨 𝙘𝙪𝙨𝙞𝙖 (Nees) Kuntze) for Initiating 𝙞𝙣 𝙫𝙞𝙩𝙧𝙤 Axenic Plantlets - Siangsuepchart, Apiradee; Wamue, Sukira; Umnat, Prajate; Ngampiboonwet, Worawut; Chuengpanya, Rodjanacorn (Burapha Science Journal, 2025)
Background and Objectives : Hom (Family : Acanthaceae, Scientific name : Strobilanthes cusia (Nees) Kuntze) is a plant producing an indigo compound that is essential for dyeing in the Morhom textile industry. Ensuring an adequate supply of Hom for dye extraction is crucial, therefore plant tissue culture techniques are employed to propagate this plant effectively. However, the mass propagation of Hom through tissue culture requires a substantial number of axenic plantlets. As a consequence, effective surface sterilization of explants is imperative for initiating in vitro contamination-free plantlets. A proper surface disinfection procedure will verify the rapid implementation of Hom tissue culture by establishing a large quantity of starting material for plant multiplication. Previous studies have examined the surface sterilization of Hom explants using sodium hypochlorite (NaOCl). While NaOCl proved effective in eliminating contamination, it induced tissue damage and cell rupture, resulting in the leakage of indigo pigment. Consequently, when these explants were cultured under aseptic tissue culture conditions, they failed to develop and ultimately died. Thus, exploring alternative chemical agents for surface sterilization of Hom explants warrants further investigation, as these agents may enhance sterilization efficiency while reducing tissue damage and explant mortality. Several studies on plant tissue culture in the Acanthaceae family have indicated that mercury(II) chloride (HgCl2) provides a high rate of both disinfection and survival of explants. Moreover, recent research has explored the application of silver nanoparticles (AgNPs) in surface sterilization processes. These nanoparticles have demonstrated effective antimicrobial properties while maintaining a high survival rate of the explants. Therefore, the objective of this study is to develop and improve the surface sterilization process of Hom explants by evaluating the effectiveness of surface sterilization using HgCl2 and Osil® (OsilR), which is an agricultural chemical and its active ingredient for eliminating microorganisms is AgNPs at 0.01% w/w. Methodology : Healthy Hom plants, exhibiting no visible signs of disease or insect damage and possessing stem heights of approximately 40–50 cm, were selected for excision of 3–4 cm long nodal segments to be used as experimental plant material. The explants were subjected to surface sterilization using either 0.1% and 0.2% (w/v) HgCl2 solutions or 10% and 15% (v/v) OsilR solutions, with soaking durations of 10 or 15 minutes, resulting in a total of eight treatment combinations. Each treatment consisted of 10 explants and was replicated three times. The nodes were subsequently cultured on Murashige & Skoog (MS) medium to evaluate the effectiveness of the surface sterilization process. After four weeks of culture, the contamination-free rate of the explants was recorded. The sterile explants were then transferred to fresh MS medium and cultured for an additional four weeks to assess their survival rate, resulting in a total culture period of eight weeks. Main Results : Surface sterilization of Hom nodal segments using HgCl2 solution resulted in an average contamination-free rate of 78.33%. In comparison, disinfection with OsilR solution provided a higher average contamination-free rate of 90.00%. Increasing both the chemical concentration and the exposure time was found to significantly enhance sterilization efficiency. Notably, treatment with 0.2% (w/v) HgCl2 solution for 15 minutes completely eliminated microbial contamination. Similarly, disinfection using 15% (v/v) OsilR solution for 10 or 15 minutes achieved a 93.33% contamination-free rate in nodal explants. The surface sterilization methods employed in this study did not cause observable damage to the explants, as evidenced by the absence of indigo pigment release. However, different surface sterilization treatments resulted in varying survival rates among contamination-free explants. Nodal segments sterilized with HgCl2 showed an overall survival rate of 28.37%, while those disinfected with OsilR exhibited a significantly higher survival rate of 95.35%. Although increasing the concentration of HgCl2 and AgNPs, along with prolonged exposure time, improved decontamination efficiency, these conditions significantly reduced explant viability. Specifically, treatment with 0.2% (w/v) HgCl2 solution for 10 or 15 minutes led to complete mortality of axenic explants. Surface sterilization of Hom nodes using 0.1% (w/v) HgCl2 solution for 10 minutes resulted in a survival rate of 64.44%, which was the highest among all explants disinfected with HgCl2 solution. In contrast, nodal segments sterilized with 10% (v/v) OsilR solution for 15 minutes or 15% (v/v) OsilR solution for 10 minutes achieved a 100% survival rate among contamination-free explants. The lowest survival rate within the OsilR-treated groups (85.56%) was observed in explants disinfected with 15% (v/v) OsilR solution for 15 minutes. Conclusions : Surface sterilization of Hom nodal segments using 15% (v/v) OsilR solution for 10 minutes was identified as the most effective method in this study. This treatment provided a high contamination-free rate of 93.33%, with 100% survival of all sterilized explants. The findings from this research can be applied to enhance the efficiency of surface sterilization protocols for Hom explants, enabling the achievement of a greater number of contamination-free and viable explants. OsilR may be considered a promising alternative chemical for the surface sterilization of Hom explants prior to introduction into tissue culture systems, thereby improving the overall potential for Hom propagation through plant tissue culture techniques.